2007
DOI: 10.1007/s10404-007-0172-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow and heat transfer in the evaporating thin film region

Abstract: The evaporating thin film region is an extended meniscus beyond the apparent contact line at a liquid/solid interface. Thin film evaporation plays a key role in a highly efficient heat pipe. A detailed mathematical model predicting fluid flow and heat transfer through the thin film region is developed. The model considers the effects of inertial force, disjoining pressure, surface tension, and curvature. Utilizing the order analysis, the model is simplified and can be numerically solved for the thin film profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 11 publications
1
48
1
Order By: Relevance
“…As the heat flux imposed on the thin film region increases, the evaporation and heat transfer rates through the evaporating thin film also increase [28]. More information on the mechanisms of heat transfer in capillary assisted grooved tubes can be found elsewhere [22,27,[29][30][31].…”
Section: Capillary-assisted Evaporationmentioning
confidence: 97%
“…As the heat flux imposed on the thin film region increases, the evaporation and heat transfer rates through the evaporating thin film also increase [28]. More information on the mechanisms of heat transfer in capillary assisted grooved tubes can be found elsewhere [22,27,[29][30][31].…”
Section: Capillary-assisted Evaporationmentioning
confidence: 97%
“…As early as 1972, Potash and Wayner (1972) expanded the Derjaguin-LandauVerwey-Overbeek (DLVO) theory (Derjaguin and Zorin 1956) to describe evaporation and fluid flow from an extended meniscus. Following this work, extensive investigations (Wayner et al 1976;Moosman and Homsy 1980;Holm and Goplen 1979;Mirzamoghadam and Catton 1988;Burelbach et al 1988;Stephan and Busse 1993;Ma and Peterson 1997;Demsky and Ma 2004;Ma et al 2008) have been conducted to further understand mechanisms of fluid flow coupled with evaporating heat transfer in thin film region. In this section, the disjoining pressure is introduced first, then the pressure across the liquid-vapor interface is tracked followed by a discussion of thin film profile, interface temperature, and heat transfer through the thin film region.…”
Section: Thin Film Evaporationmentioning
confidence: 99%
“…Using the procedure described above (Ma et al 2008), the governing equation shown in Eq. (2.217) can be solved with boundary condition shown in Eq.…”
Section: Momentum Conservation Modelmentioning
confidence: 99%
“…Chakraborty and Som (2005), in a more recent study, linked the rate of evaporation from the free surface of the thin liquid film into a medium of air and water vapor maintained throughout at a temperature below the saturation temperature corresponding to its existing pressure with the vapor phase mass diffusion. Ma et al (2007), in another recent investigation, developed a detailed model to determine the effects of inertial force, interfacial thermal resistance, surface tension, and disjoining pressure on the thin film profile, interfacial temperature variation, fluid flow, and the local heat transfer rates. Wang et al (2007) investigated an evaporating meniscus in a microchannel through an augmented Young-Laplace equation, by employing a kinetic theory based expression for mass transfer across the liquid-vapor interface.…”
Section: Introductionmentioning
confidence: 99%